Orientação metodológica para construção e leitura de mapas temáticos - Rosely Sampaio Archela; Hervé Théry (Confins)
The article systematizes the fundamental concepts of the cartographic process which must be respected in the construction of maps if they are to be useful for the analysis and the comprehension of geographical space. It establishes a correlation between the maps produced with the assistance of free softwares, graphic semiology and the preparation made by the "manufacturer" of the maps. A didactic analysis introduces a classification of the types of maps according to the mode of expression, scale, contents, type of implantation, level of organization, visual variables and methods of cartography, in order to contribute to the training of the "manufacturers" and "readers" of charts. Finally, it analyzes the cartographic language present in maps at several scales.